PROBLEMATIKA PEPMBELAJARAN TATAP MUKA TERBATAS MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Supri Supri; Syamsu Sanusi; Fauziah Zainuddin (Kelola: Journal of Islamic Education Management, 2023)
This research discusses the Problems of Limited Face-to-Face Learning in Islamic Religious Education Subject for Students at UPT SMA Negeri 6 Palopo. This study aims to (a) find out the application of limited face-to-face learning on Islamic religious education (PAI) subjects to the students of UPT SMA Negeri 6 Palopo. (b) knowing the problems of limited face-to-face learning on Islamic religious education (PAI) subjects at UPT SMA Negeri 6 Palopo (c) limited face-to-face learning solutions for Islamic religious education (PAI) subjects for students at UPT SMA Negeri 6 Palopo. This research is a descriptive qualitative research. The research location is UPT SMA Negeri 6 Palopo. Subjects and objects of research are educators and students. Data collection techniques used observation, interviews and documentation. In this study, the data processing techniques used were data reduction, data presentation and conclusion drawing as well as data verification and analysis. The results showed that UPT SMA Negeri 6 Palopo implemented a hybrid learning system, namely a limited face-to-face learning system and online learning with odd-even sessions. Problems in the limited face-to-face from educators are the limitations in controlling students who take online learning, the concentration is divided so that it is less focused, the delivery of material seems rushed because of the limited time duration. Meanwhile, from students, there are demands to adapt to the type of learning they receive. Problems in learning religious education are the lack of students' understanding of the material provided, lack of motivation, there are still students who are not proficient in reading and memorizing prayers in the material for handling corpses. Efforts to overcome the problems of Limit. Face-to-Face Learning, namely for students who have a turn to study online, the learning model is in the form of presenting short material in the form of important points through WA groups or other applications and dominant in assignments. Meanwhile, those who get a face-to-face turn are limited to focusing on explanations and deepening of material and discussions. Persuasive approach, giving advice, enthusiasm and motivation.